Islamic Values in the Use of Four Steps Teaching Material Development (4-STMD) Method in Teaching Stoichimetry Material - Siti Suryaningsih; Buchori Muslim; Nurul Anjar Wati (TARBIYA: Journal of Education in Muslim Society, 2020)
AbstractThe Integration of Islam and Science has been applied in several countries both domestically and abroad. The Chemistry  Education Study Program has not yet implemented the integration of Islam and science, especially in the stoichiometry concept. Therefore, Chemistry Education at the Syarif Hidayatullah State Islamic University of Jakarta added the Program  Learning Outcome (PLO) is in the form of mastering the basic concepts of scientific, Islamic, and Indonesian integration in basic chemistry concept. This study aims to analyze the integration of Islam and science on the stoichiometry concept using the 4-STMD method. The 4-STMD method consists of the selection stage, the structuring stage, the characterization stage, and the reduction stage. The subjects used were 49 students of chemical education class of 2016/2017, one validator of integration experts, and three validators of media experts. The instrument used was in the form of mortar test questionnaire sheets and validation sheets for integration experts and media experts. The result shows that at the selection stage, the determination of the main textbook is the book written by Raymond Chang. In the structuring phase, a draft of the Islamic integrated teaching concept is obtained that ready to be tested. At the characterization, stage have a high level of comprehension test of 80.6% with the easy category. This shows that the integrated Islamic stoichiometry concept does not need to be carried out at the reduction stage. The results of the stoichiometric material feasibility test were 96.74% with very decent criteria. The integrated Islamic stoichiometry concept can be used as a reference source in the learning of integrated Islamic chemistry.AbstrakIntegrasi Islam dan Sains sudah diterapkan dibeberapa negara baik dalam negeri maupun luar negeri. Program Studi Pendidikan Kimia belum menerapkan integrasi islam dan sains terutama dalam materi stoikiometri. Oleh sebab itu, Pendidikan kimia Universitas Islam Negeri Syarif Hidayatullah Jakarta menambahkan Program Learning Outcome (PLO) berupa menguasai konsep dasar integrasi keilmuwan, keislaman, dan keindonesiaan pada materi kimia dasar. Penelitian ini bertujuan untuk menganalisis integrasi islam dan sains pada materi stoikiometri menggunakan metode 4-STMD.  Metode  4-STMD  terdiri dari tahap seleksi, tahap strukturisasi, tahap karakterisasi, dan tahap reduksi. Subjek yang digunakan adalah 49 mahasiswa pendidikan kimia angkatan 2016/2017, satu validator ahli integrasi, dan tiga validator ahli media. Instrumen yang digunakan berupa lembar angket tes rumpang dan lembar validasi ahli integrasi serta ahli media.  Hasil menunjukkan bahwa pada tahap seleksi dilakukan penentuan buku teks utama yaitu buku  karangan Raymond Chang. Pada Tahap stukturisasi diperoleh draft bahan ajar terintegrasi keislaman yang siap diujikan. Pada tahap karakterisasi  memiliki uji keterpahaman tingkat tinggi sebesar 80,6 % dengan kategori mudah. Hal ini menunjukkan materi stoikiometri terintegrasi keislaman tidak perlu dilakukan tahap reduksi. Hasil uji kelayakan materi stoikiometri sebesar 96,74 % dengan kriteria sangat layak. Materi stoikiometri terintegrasi keislaman yang dihasilkan dapat digunakan sebagai sumber referensi dalam pembelajaran kimia  terintegrasi keislaman. How to Cite: Suryaningsih, S., Muslim, B., Wati, N. A. (2020).   Islamic Values in the Use of Four Steps Teaching Material Development (4-STMD) Method in Teaching Stoichimetry Material. TARBIYA: Journal of Education in Muslim Society, 7 (1), 78-87. doi:10.15408/tjems.v7i1.14066.